Resolving Seismic Anisotropy of the Lithosphere–Asthenosphere in the Central/Eastern Alps Beneath the SWATH-D Network - Link, Frederik; Rümpker, Georg (Frontiers in Earth Science, 2021)
The Alpine orogeny is characterized by tectonic sequences of subduction and collision accompanied by break-off events and possibly preceded by a flip of subduction polarity. The tectonic evolution of the transition to the Eastern Alps has thus been under debate. The dense Swath-D seismic network as a complementary experiment to the AlpArray seismic network provides unprecedented lateral resolution to address this ongoing discussion. We analyze shear-wave splitting of this data set including stations of the AlpArray backbone in the region to obtain new insights into the deformation at depth from seismic anisotropy. Previous studies indicate two-layer anisotropy in the Eastern Alps. This is supported by the azimuthal pattern of the measured fast-axis direction across all analyzed stations. However, the temporary character of the deployment requires a joint analysis of multiple stations to increase the number of events adding complementary information of the anisotropic properties of the mantle. We, therefore, perform a cluster analysis based on a correlation of energy tensors between all stations. The energy tensors are assembled from the remaining transverse energy after the trial correction of the splitting effect from two consecutive anisotropic layers. This leads to two main groups of different two-layer properties separated approximately at 13°E. We identify a layer with constant fast axis direction (measured clockwise with respect to north) of about 60° over the whole area, with a possible dip from West to East. The lower layer in the West shows N-S fast direction and the upper layer in the East shows a fast axis of about 115°. We propose two likely scenarios, both accompanied by a slab break-off in the Eastern part. The continuous layer can either be interpreted as frozen-in anisotropy with lithospheric origin or an asthenospheric flow evading the retreat of the European slab that would precede the break-off event. In both scenarios the upper layer in the East is a result of a flow through the gap formed in the slab break-off. The N-S direction can be interpreted as asthenospheric flow driven by the retreating European slab but might also result from a deep reaching fault-related anisotropy.